Case reportMalignant metastasizing solitary fibrous tumors of the liver: a report of three cases - Maccio, Livia; Bonetti, Luca Reggiani; Siopis, Elena; Palmiere, Cristian (Polish Journal of Pathology, 2015)
Solitary fibrous tumors are rare neoplasms of mesenchymal origin that have been reported in various other extrathoracic sites, including the liver. We present a case series of three malignant solitary fibrous tumors of the liver, occurring in two women 74 and 80 years old and one 65-year-old man. No clinical features were predictive of malignancy except the large sizes and synchronous presence of lung metastases in two of the three cases. Histological examinations revealed the presence of high pleomorphic cellularity with nuclear atypia, necrosis and high mitotic ratios. All patients died of disease progression.